Evaluasi Pasca Huni terhadap Kinerja Fungsional Bangunan Panti Wreda Widhi Asih Surakarta - Anita Dianingrum; Ghaitsa Rahima; Salwa Rahmanisa (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2026)
Post-Occupancy Evaluation of the Functional Performance of Panti Wreda Widhi Asih SurakartaElderly care facilities require a built environment that ensures comfort, safety, and accessibility to support residents' quality of life. This study evaluates the Panti Wreda Widhi Asih Surakarta through physical, environmental comfort, and accessibility aspects using the Post-Occupancy Evaluation (POE) method with a mixed-methods approach comprising observation, interviews, questionnaires, and environmental parameter measurements. Results indicate that although the physical condition of the building was rated reasonably good, most environmental parameters did not meet the standards, particularly high indoor temperatures (32–35°C), minimal air circulation, noise levels exceeding the threshold, and inadequate accessibility elements. Design interventions based on thermal comfort and universal design are needed to improve the quality of the elderly residential environment.